Increasing Basic Knowledge of Students with the Inquiry Learning Model on the Nature of Change of Material in the Form of Objects with the Aid of Game Quizizz/ Meningkatkan Pengetahuan Dasar Mahasiswa dengan Model Pembelajaran Inkuiri - Maylana Nurfariha; Nirwana Anas; Siti Fatonah (Laboratorium Pendidikan Fakultas Ilmu Tarbiyah dan Keguruan Colaboration with Persatuan Pranata Laboratorium Pendidikan Indonesia Tingkat Nasional, 2022)
This research was conducted to know the extent to which students have reached their basic knowledge because, if it is too late, it will become a risk for evaluation and improvement in the future. They also will find it difficult when teaching their students later. The purpose of this study was to determine the implementation of the inquiry learning model and the student's basic knowledge about the material